Dysbiosis of Intestinal Microbiota and Decreased Antimicrobial Peptide Level in Paneth Cells during Hypertriglyceridemia-Related Acute Necrotizing Pancreatitis in Rats - Huang, Chunlan; Chen, Jing; Wang, Jingjing; Zhou, Hui; Lu, Yingying; Lou, Lihong; Zheng, Junyuan; Tian, Ling; Wang, Xingpeng; Cao, Zhongwei; Zeng, Yue (Frontiers in Microbiology, 2017)
Hypertriglyceridemia (HTG) aggravates the course of acute pancreatitis (AP). Intestinal barrier dysfunction is implicated in the pathogenesis of AP during which dysbiosis of intestinal microbiota contributes to the dysfunction in intestinal barrier. However, few studies focus on the changes in intestine during HTG-related acute necrotizing pancreatitis (ANP). Here, we investigated the changes in intestinal microbiota and Paneth cell antimicrobial peptides (AMPs) in HTG-related ANP in rats. Rats fed a high-fat diet to induce HTG and ANP was induced by retrograde injection of 3.5% sodium taurocholate into biliopancreatic duct. Rats were sacrificed at 24h and 48h, respectively. Pancreatic and ileal injuries were evaluated by histological scores. Intestinal barrier function was assessed by plasma diamine oxidase activity (DAO) and D-lactate level. Systemic and intestinal inflammation was evaluated by TNFα, IL-1β and IL-17A expression. 16S rRNA high throughput sequencing was used to investigate changes in intestinal microbiota diversity and structure. AMPs (α-defensin5 and lysozyme) expression was measured by real-time PCR and immunofluorescence. The results showed that compared with those of normal-lipid ANP (NANP) groups, the HTG-related ANP (HANP) groups had more severe histopathological injuries in pancreas and distal ileum, aggravated intestinal barrier dysfunction and increased TNFα, IL-1β and IL-17A expression in plasma and distal ileum. Principal component analysis (PCA) showed structural segregation between the HANP and NANP group. α-diversity estimators in the HANP group revealed decreased microbiota diversity compared with that in NANP group. Taxonomic analysis showed dysbiosis of intestinal microbiota structure. In the HANP group, at phyla level, Candidatus_Saccharimonas and Tenericutes decreased significantly, whereas Actinobacteria increased. At genus level, Allobaculum, Bifidobacterium and Parasutterella increased significantly, while Alloprevotella, Anaerotruncus, Candidatus_Saccharimonas, Christensenellaceae_R-7_group, Rikenellaceae_RC9_gut_group, Ruminiclostridium_5, Ruminococcaceae_UCG-005 and Ruminococcaceae_UCG-014 decreased. Compared with those in the NANP rats, mRNA expression of lysozyme and α-defensin5 and protein expression of lysozyme decreased significantly in the HANP rats. Moreover, in the NANP rats and the HANP rats, Allobaculum abundance was inversely correlated with lysozyme expression, while Anaerotruncus abundance was positively correlated with it by Spearman test. In conclusion, intestinal microbiota dysbiosis and decreased antimicrobial peptides of Paneth cells might participate in the pathogenesis of intestinal barrier dysfunction in HTG-related ANP.